The Representation of Positive Politeness in The Linguistic Expressions Used in an Elt Textbook for The Junior High School - Bintang Anugrah Saputra (Fakultas Ilmu Pendidikan Dan Keguruan, 2026)
This research examines the use of positive politeness strategies in the English Language Teaching (ELT) textbook “When English Rings a Bell” for seventh-grade junior high school students. This research aims to identify and analyze the types of positive politeness strategies reflected in the textbook, utilizing Brown and Levinson's (1987) theoretical framework as the basis for analysis. This study employed a descriptive qualitative approach, in which data were collected through the analysis of textbook dialogue documents and speech bubbles. The analytical process was guided by the framework introduced by Miles and Huberman (1994), which involves three stages: reducing the data, presenting the data, and drawing conclusions. The results indicate that the dialogues demonstrate nine of the fifteen positive politeness sub-strategies, with a total of 33 instances identified. Among these strategies, exaggerating the listener’s interest, approval, or sympathy appears most frequently, with nine occurrences. Following this, the strategy of paying attention to the listener’s interests, needs, wishes, or goods and using indicators of in-group identity each appear five times. Moreover, the strategies of seeking agreement and confirming or showing awareness and consideration of the listener’s wishes occur four times each. In addition, the strategies of intensifying interest to the listener and being optimistic are found twice each. Meanwhile, the strategies of offering or promising and including both the speaker and the listener in an activity appear only once each. Conversely, the strategies of avoiding disagreement, raising common ground, using humour or joking, giving or asking for reasons, assuming or asserting reciprocity, and giving a gift to the listener do not appear at all in the analyzed dialogues. These results suggest that the textbook emphasizes strategies that foster empathy, attentiveness, and group solidarity—values consistent with Indonesian sociocultural norms. In line with Brown and Levinson’s (1987) notion of positive politeness as a means of expressing closeness and shared identity, the textbook effectively incorporates politeness expressions that promote harmony and cooperation in communication. Therefore, When English Rings a Bell is considered pedagogically appropriate for introducing students to both linguistic and pragmatic aspects of English use. Future research is recommended to investigate how politeness strategies are presented in textbooks across various grade levels or within other ELT instructional material. Through such studies, broader insights may be obtained regarding how politeness contributes to the development of communicative competence and character education within language learning contexts.
Reupload file repositori 15 Mei 2026_Maya Validasi repository 18 Juni 2026_Naomy/Firly
Keywords: English Language Teaching